Abbattere muri (in)visibili Confini, migrazioni e arte contemporanea (Altre Modernità, 2021)
Contemporary art that turns its attention to investigating the geopoliticalsituation of today’s world has long worked on the visible and invisible boundaries thatseparate people, societies and cultures. The production on the theme of the reificationof transnational borders through physical barriers (such as walls) or natural barriers(such as the sea) is now vast both for the quantity of works produced and for theheterogeneity of the forms in which it expresses itself. For the seriousness of theconsequences of their management on the people who try to cross them and for thescope of the discourses that, initially local, prove to be potentially universal, two areasrepresent emblematic cases: the border between Mexico and the United States and theMediterranean basin.Contemporary art focuses on these areas as well, with contributions that oftenresonate with those from other disciplines (anthropology, border studies). Referring tosome of the works realized there in the last twenty years, some recurrences will beidentified in the speeches promoted (denunciation of contingent situations, criticism ofcolonialism harbinger of current discriminations, analogies that connect human beingsbeyond their cultural variability), coming to identify the final common denominator ofthese works in the will to question and break down not only the walls, but also theborders, seen as remnants of colonial ways of relationship between human beings nolonger acceptable.
Keywords: border; international migrations; cultural identity; contemporary art; U.S.- Mexico border; Mediterranean Sea